2021
DOI: 10.2147/jir.s316816
|View full text |Cite
|
Sign up to set email alerts
|

Monomeric CRP Aggravates Myocardial Injury After Myocardial Infarction by Polarizing the Macrophage to Pro-Inflammatory Phenotype Through JNK Signaling Pathway

Abstract: A polarized macrophage response plays a critical role in the pathophysiological process of myocardial infarction (MI). Several studies have shown a pro-inflammatory role for monomeric C-reactive protein (mCRP) in cardiovascular disease. However, the mechanism of how mCRP regulates macrophage phenotype switching remains unknown. In the present study, the effect of mCRP on macrophage polarization and its pathological function in myocardial repair after myocardial infarction was investigated. Methods: MI was indu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 38 publications
1
12
0
Order By: Relevance
“…Serum Hcy is considered a commonly used specific indicator for assessing cardiovascular disease outcomes [ 28 ]. CRP is a more sensitive indicator of human inflammatory response [ 29 ]. The results of this study show that bisoprolol can effectively regulate serum Hcy and CRP levels, further confirming the superiority of bisoprolol in the treatment of myocardial infarction with cardiac insufficiency.…”
Section: Discussionmentioning
confidence: 99%
“…Serum Hcy is considered a commonly used specific indicator for assessing cardiovascular disease outcomes [ 28 ]. CRP is a more sensitive indicator of human inflammatory response [ 29 ]. The results of this study show that bisoprolol can effectively regulate serum Hcy and CRP levels, further confirming the superiority of bisoprolol in the treatment of myocardial infarction with cardiac insufficiency.…”
Section: Discussionmentioning
confidence: 99%
“…This suggests that exosomes from the uterine cavity in endometriosis could inhibit macrophage M1 polarization by inhibiting the JNK pathway, and this effect can be treated with anisomycin. Zha et al demonstrated that the activation of the JNK signaling pathway enhances macrophage M1 polarization [ 33 ]. Chen et al also found that the inhibition of JNK phosphorylation was linked to decreased M1 macrophages, which was consistent with our results [ 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…Recently, Melnikov et al ( 13) described significantly increased concentrations of blood circulating mCRP-bound macrophages in patients with coronary artery disease, whilst Zha et al (14), showed increased infiltration of macrophages polarized to the inflammatory M1 phenotype (induced through the JNK signaling pathway activation) in mice following experimental coronary artery occlusion and intra-venous treatment with mCRP; and this was associated with increased myocardial infarct size, scar and fibrosis. These observations also showed the presence of mCRP in human infarcted myocardial tissue surrounding myocytes in post-mortem tissues, identified by IHC using standard manufactured CRP-binding antibodies.…”
Section: Evidence Of the Disease Modifying Behavior Of Mcrpmentioning
confidence: 99%